Large firm dominance on country's entrepreneurship potentials - Raymond E. Gaspar (Journal of Global Entrepreneurship Research, 2017)
This paper aims to determine whether countries where large firms are very dominant have less entrepreneurial activities. There is anecdotal evidence that the continued decline in the business dynamism or the number of start-ups in the United States is said to be partly attributed to large firms. One key explanation is that the regulatory environment tends to favor existing large firms - an environment that allows near monopolies and a protection of tiny entrepreneurial elite. Using the Global Entrepreneurship Monitor (GEM) data together with the World Bank - International Finance Corporation's MSME country indicators, I empirically test whether large firm dominance influences entrepreneurial activities as well as intentions. Using fixed effects regression analysis on unbalanced panel of 40 countries over the period 2002-2007, I found that the entrepreneurship potential of a country is potentially at risk if the growth of large firms' stake in the economy is left unchallenged. In particular, a one percentage point increase in the share of large firms to total employment is associated with 0.35 percentage point lower total early-stage entrepreneurial activity rate, holding other factors constant. Also, worth noting is the sensitivity of entrepreneurial intentions to large firm dominance. A one percentage point increase in the share of large firms to total employment dampens (i.e., by 0.56 percentage point) intentions of latent entrepreneurs to start a business within the next 3 years, other factors remaining constant. This second-order effect of large firm dominance depends heavily on the country's institutions. Thus, it is critical for governments to foster a dynamic system that guarantees free competition and rewards creativity. Likewise, it is necessary to review and amend policies that seem to favor large firms that compromise the establishment as well as growth of smaller enterprises.
Keywords: 650; Large firm dominance; Entrepreneurship; Global Entrepreneurship Monitor